La lúdica como herramienta pedagógica para fortalecer el desarrollo socio-afectivo de los estudiantes de transición de la Institución Educativa Distrital Cristo Rey (2020)
Play is defined as the set of activities mediated by gratifying experiences such as play, leisure and other pleasant activities that contribute to the learning and socio-emotional development of children. In this way, the present research aims to determine the influence of play to strengthen the socio-affective development of Transitional students of I.E.D. Christ the King. To achieve this, a descriptive qualitative methodology was used, using as data collection instruments an observation guide and interviews applied to 4 teachers and 75 transitional grade students. Among the results obtained, it was found that the institution takes into account the socio-affective dimension, however, teachers tend to be traditionalists in their methodologies and do not include recreational activities in their classes, which is related to the fact that there are no projects in the institution that promote them, despite this, teachers recognize the importance of play in the socio-affective development of students, so when carrying out this type of activities they seek to promote children's self-esteem, self-concept and social skills, finally , it is evidenced that students like to participate in games and artistic activities, which become a motivator for them to attend classes, likewise, they enable positive relationships with their peers.